Phenotypic variation of tuberous sclerosis in a single extended kindred. Issue 10 (October 1994) - Smalley, S L; Burger, F; Smith, M
Abstract : Tuberous sclerosis complex (TSC) is an autosomal dominant disorder with a great degree of phenotypic variability. Given the presence of two gene loci underlying this disorder, locus heterogeneity may account for some of the variability. However, significant within family variation suggests that different genes do not explain the majority of this variation. The purpose of this research is to identify physical and behavioural variation in expression of TSC in a single large extended kindred. TSC in this kindred is cosegregating with markers localised to chromosome 16p13.3. The expression of TSC in this kindred is quite variable with a substantial proportion of persons showing very mild physical expression of TSC. In contrast to very mild physical expression of TSC in some family members, there is a significant clustering of psychiatric disorders among persons affected with TSC compared to their unaffected relatives. This finding, coupled with the mild physical expression of TSC in some family members, supports a hypothesis that the TSC2 gene may present phenotypically as mild skin signs and significant behavioural problems.